Striatal NMDA receptors gate cortico-pallidal synchronization in a rat model of Parkinson's disease - Zold, Camila Lidia (2012)
Anomalous patterns of synchronization between basal ganglia and cortex underlie the symptoms of Parkinson´s disease. Computational modeling studies suggest that changes in cortical feedback loops involving trans-striatal and trans-subthalamic circuits bring up this anomalous synchronization. We asked whether striatal outflow synchronizes globus pallidus neurons with cortical activity in a rat model of Parkinson´s disease. We found that striatal firing is highly increased in rats with chronic nigrostriatal lesion and that this hyperactivity can be reduced by locally infusing a competitive NMDA receptor antagonist. Moreover, NMDA receptor-dependent striatal output had frequency dependent effects on distinct pathological patterns of cortico-pallidal coupling. Blockade of striatal NMDA receptors almost completely abolished an anomalous ~ 1 Hz cortico-pallidal anti-phase synchronization induced by nigrostriatal degeneration. Moreover, under striatal NMDA receptor blockade, synchronization with 2.5?5 Hz cortical oscillations falls to negligible levels and oscillations at 10?20 Hz are markedly attenuated, whereas beta synchronization (with a peak at ~ 26 Hz) is marginally reduced. Thus, tonic activation of striatal NMDA receptors allows different forms of anomalous oscillations along the cortico-striato-pallidal axis. Moreover, the frequency dependent effects of NMDA receptors suggest that low and high frequency parkinsonian oscillations stem from partially different mechanisms. Finally, our results may help to reconcile views about the contributions of changes in firing rate and oscillatory synchronization to Parkinson´s disease symptoms by showing that they are related to each other.